Potentiating Interaction of Ethoxydol and Rosuvastatin in an Experimental Model of Langendorf-isolated Rat Heart Total Ischemia-reperfusion - Soldatov, Vladislav O. (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Ethoxidol is a promising cardioprotective drug, the pharmacological activity of which is based on antihypoxic and antioxidant action. Aim and Objective: This study aims to study the cardioprotective activity of ethoxydol in monotherapy and combination of ethoxidol and rosuvastatin using Langendorf-isolated rat heart model. Materials and Methods: Langendorf-isolated hearts were divided into four groups: (I) Control, (II) ethoxidol in a small dose (1 × 10−4 g/l), (III) ethoxydol in a large dose (3.8 × 10−4 g/l), and (IV) combined use of a large dose of ethoxidol (3.8 × 10−4 g/l) and rosuvastatin (4 × 10−5 g/l). Ischemic lesions were modeled with a 60-min pause in heart perfusion. For the study of cardioprotective activity, the contractile function of the heart and NADPH activity of myocardiocytes was evaluated by staining sections with triphenyltetrazolium chloride. Results: The dose-dependent pharmacological efficacy of ethoxydol was established. In addition, the combination of ethoxydol at a concentration of 3.8 × 10−4 g/l with rosuvastatin (4 × 10−5 g/l) had the greatest effect on the reduction of contractility during the reperfusion period. Conclusion: The study of cardioprotective activity showed that in vitro ethoxydol at a dose of 3.8 × 10−4 g/l can significantly improve the morphofunctional state of cardiomyocytes, which is manifested in an increase in the proportion of postischemic cardiac resumption, reduction of ischemic contracture, and recovery of contractility during the reperfusion period.